Food and nutritional contexts for primary health care users with type 2 diabetes mellitus: educational booklet (Revista Brasileira Multidisciplinar, 2025)
Low knowledge of type 2 Diabetes Mellitus (DM2) is associated with inefficient glycemic control and may be related to non-adherence to nutritional treatment. The use of validated printed educational materials is one way of approaching topics that can contribute to individuals' knowledge and add value to health services. This study focused on constructing and validating an educational booklet on food and nutritional contexts for Primary Health Care (PHC) users with DM2. The booklet was developed by the researchers and validated by a group of judges made up of nutritionists and nurses. The evaluation considered the following domains: scientific accuracy, content, literary presentation, illustration, specific and comprehensible material and quality of information. After the judges' assessment, the Content Validity Index (CVI) was applied. Acceptable agreement was obtained when each item in the instrument had a minimum CVI value of 0.80. Although the Educational Booklet had a high overall CVI (0.99), the judges requested adjustments related to improving the content, including adjusting the spelling of the text, reformulating texts and figures to make them easier to understand and changing terms or expressions to make them simpler to read, in order to favor interpretation by the target audience as much as possible. The conclusion is that the Educational Booklet on food and nutritional contexts for PHC users with DM2, validated by expert judges, is a substantial tool to be used as a health promotion measure for this target audience.
Keywords: Food and nutrition education; Type 2 diabetes mellitus; Validation study; Teaching materials; Primary health care